2013
DOI: 10.7235/hort.2013.12200
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Secondary Metabolites in Various Parts of 'Seolhyang' Strawberry Plants

Abstract: Abstract. The objective of this study was to identify the content of phenolic and volatile organic compounds in edible and non-edible parts of 'Seolhyang' strawberry plants. We performed a comparative chemical analysis of the compounds found in roots, leaves, petioles, runners, and unripe and ripe fruits during vegetative propagation and reproductive growth. The contents of ellagic and gallic acids in the leaves of runner plants during vegetative propagation were 7.36 ± 1.10 and 5.07 ± 3.66 mg·g -1 FW, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Brown et al (2003) reported that young leaves of Arabidopsis have various secondary metabolites compared to old leaves, probably due to the re-allocation of secondary metabolites to decrease feeding by herbivores. Young leaves of strawberry plants also included greater content of phenolic compounds than old leaves (Kim et al, 2013). Antimicrobial activity of caffeic acid has been tested against various fungi and bacteria (Harrison et al, 2003;Kim et al, 2012;Rauha et al, 2000;Widmer and Laurent, 2006).…”
Section: The Contents Of Phenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brown et al (2003) reported that young leaves of Arabidopsis have various secondary metabolites compared to old leaves, probably due to the re-allocation of secondary metabolites to decrease feeding by herbivores. Young leaves of strawberry plants also included greater content of phenolic compounds than old leaves (Kim et al, 2013). Antimicrobial activity of caffeic acid has been tested against various fungi and bacteria (Harrison et al, 2003;Kim et al, 2012;Rauha et al, 2000;Widmer and Laurent, 2006).…”
Section: The Contents Of Phenolic Compoundsmentioning
confidence: 99%
“…For instance, the leaves of strawberry and carrot include higher contents of phenolic compounds than edible parts (Kähkönenet al, 1999;Kim et al, 2013). The previous researches, however, have analyzed the contents of secondary metabolites in ripe fruits of tomato plants but few studies have reported the metabolites in inedible parts such as leaves, internodes, unripe fruits, and roots.…”
Section: Introductionmentioning
confidence: 99%
“…The fiber content, in association with bioactive compounds, helps regulate blood sugar levels, which is important for controlling type 2 diabetes (Baicu & Popa, 2018). Various secondary metabolites are present in strawberries, including anthocyanins, ellagic acid, ellagitannins, and gallic acid, in varying amounts based on the strawberry cultivar and the ripening stage of the fruits (Kim et al., 2013). These secondary metabolites act as antioxidants that help to reduce inflammation and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%